Efforts To Increase The Coverage Of The Pregnant Women's Health Program (ANC) During The COVID-19 Pandemic At The Health Office Of The Kampar Regency - meldy, meldy; Mitra, Mitra; Afridayanti, Afridayanti (Jurnal Ilmu Kesehatan, 2022)
Background: According to the 2020 Yankes Guidelines, MCH services are still carried out with due observance of health protocols. Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are indicators of Maternal and Child Health (KIA) status that can describe the quality and accessibility of health care facilities. Based on a preliminary survey that the author has conducted through document searches on November 22, 2021 from the Maternal Mortality Rate Program section at the Kampar District Health Office, it is known that in 2020 the achievement of the MCH program has not yet reached the target of the Ministry of Health. Objectives: Identify problems, prioritize problems, determine alternative solutions to problems, and make an Intervention Plan (Plan of Action) in accordance with alternative solutions to problems related to the MCH Program during the Covid-19 Pandemic Period at the Kampar District Health Office. Methods: Qualitative method, using document tracing data sources, direct observations and field observations in the Maternal Mortality Rate program. The informants are the Head of the Kampar District Health Office, the Head of the Public Health Division, and the holder of the Maternal Mortality Rate Program. Results: The achievement of the Maternal Mortality Rate program is still low because during the COVID-19 pandemic, so that the implementation of the MCH program is not yet optimal. Solving the problem of the low achievement of the Maternal Mortality Rate program at the Kampar District Health Office by making a Proposed Work Plan (RUK) or designing a Plan Of Action (POA).Conclusion : The low achievement of the MCH program is due to the non-optimal implementation of the Antenatal care (ANC) program, the non-optimal implementation of the obstetric complications program and the non-optimal implementation of the Neonatal Complications program. The recommendation is that it is hoped that the Head of the Kampar District Health Office will increase the number of officers for and analyze the needs of health workers